Paradoxical effect of anti-inflammatory drugs on IL-6 mRNA expression in patients with PTSD during treatment - Rhein, Cosima; Apelt, Isabella; Werner, Franziska; Schäflein, Eva; Adler, Werner; Reichel, Martin; Schug, Caterina; Morawa, Eva; Erim, Yesim (Journal of Neural Transmission, 2024)
The pathophysiology of posttraumatic stress disorder (PTSD) is associated with the activation of the innate immune system, including cytokines like interleukin 6 (IL-6). However, the role of IL-6 in the etiology and treatment of PTSD still remains elusive. We conducted a prospective controlled trial to investigate the development of IL-6 during psychosomatic treatment in individuals with PTSD in comparison with individuals without PTSD. We assessed IL-6 mRNA expression before and after 2 months of psychosomatic treatment in individuals with and without PTSD. Severities of PTSD and depressive symptoms were assessed in parallel. Linear mixed regression was applied for statistical analysis, including the factors diagnosis PTSD and pre–post treatment after subgrouping for intake of anti-inflammatory drugs. The development of IL-6 mRNA expression during treatment was affected by the use of anti-inflammatory drugs. In the subgroup without intake of anti-inflammatory drugs, no significant statistical treatment effect in individuals with and without PTSD emerged. In the subgroup of individuals taking anti-inflammatory drugs, a significant interaction effect of the factors pre–post treatment and diagnosis PTSD was observed. Whereas IL-6 mRNA expression in individuals without PTSD decreased according to amelioration of symptoms, IL-6 mRNA expression in individuals with PTSD increased significantly during treatment, in opposite direction to symptom severity. Anti-inflammatory drugs might affect IL-6 mRNA expression in individuals with PTSD in a paradoxical way. This study offers a further piece of evidence that IL-6 could be involved in the pathophysiology of PTSD and PTSD-specific immunologic molecular mechanisms.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Anti-inflammatory drugs; Interleukin 6; Posttraumatic stress disorder; Psychotherapy; Therapy outcome